Firm size moderates tax avoidance and profitability impact on cost of debt: indonesian healthcare and property - Muhammad Iqbal Pratama; Heru Tjaraka (Jurnal Akademi Akuntansi, 2026)
Purpose: This study analyzes the effect of tax avoidance and profitability on the cost of debt, with firm size as a moderator, in Indonesian healthcare and property firms 2020–2024. Methodology/approach: A quantitative PLS-SEM analysis is conducted using 245 firm-year observations from 49 firms. Findings: Tax avoidance increases the cost of debt, while profitability reduces it. Firm size amplifies both relationships, strengthening the penalty for tax avoidance and the reward for profitability. Leverage raises and operating cash flow lowers borrowing costs. Practical and Theoritical contribution/Originality: The originality lies in revealing firm size as an asymmetrical amplifier, challenging the view of size as a uniform risk buffer. This refines agency and signaling theories and provides practical guidance for managers and creditors in emerging markets. Research Limitation: The study is limited to two sectors in one emerging market, relies on a single tax avoidance proxy, spans a crisis period, and excludes macroeconomic and governance variables.